Mobilizing a fast policy fix: Exploring the translation of 10-year plans to end homelessness in Alberta, Canada. (May 2020) - Evans, Joshua; R Masuda, Jeffrey
The management of homelessness has taken various forms over time. In 2003, the U.S. federal government significantly shifted its approach, ambitiously committing to end homelessness within 10 years by targeting the chronically homeless using the Housing First model. This approach to homelessness has rapidly spread across North America and beyond. This article is concerned with how the mobility of these 10-year plans has been realized. Drawing onPeck and Theodore's concept of "fast policy, " and borrowing perspectives developed in actor-network theory, the article develops a case study of Alberta, Canada, to chronicle how 10-year plans were translated through a dense network of political alignments, socio-technical expertise, and statistical inscriptions. A close examination of these translations invites us to problematize this socio-technical infrastructure as a powerful mode of adaptive governance closely associated with the dynamism of neoliberalism itself.